From Personal to Social Transformation: A Phenomenological Study on the Life of ‘Kyai Kampung’ - Kafid, Nur (Universitas Negeri Semarang, 2014)
The study aims to explore phenomenologically the experiences of “kyai kampong” at Madrasah ‘Tasywiqul Mustarsyidin’ Demak, Central Java, Indonesia. This study specifically emphasizes how personal transformation could result into larger social transformation. The experiences of Kyai Kampung at Maredan Village, Demak, Central Java reveals that certain principles of life drawn from a rich religious tradition have empowered local religious leader to transform himself and his community. Religious tradition and local wisdom shape their daily life and self-identity. Under the pressure of modernization and globalization values which are dominated by the value of consumerism and materialism, the kyais are still holding strongly the value of ‘ikhlas’ in their teaching tradition. Even though they strongly hold Islamic religious teaching, they do not ignore the importance of local culture in their daily lives.Studi ini, secara fenomenologis dilakukan untuk mengeksplor pengalaman hidup (dalam mengajar) para Guru di Madrasah ‘Tasywiqul Mustarsyidin’ Desa Maredan, Kabupaten Demak, Jawa Tengah, dengan menekankan pada proses refleksi sosial-keagamaan yang menghasilkan adanya transformasi personal dan sosial. Pengalaman hidup para Kyai Kampung ini sangatlah unik. Tradisi dan kearifan lokal menjadi ciri khas identitas dan gaya hidup mereka sehari-hari. Meski arus modernisasi dan globalisasi yang didominasi oleh nilai-nilai konsumerisme dan materialisme juga deras mengalir dalam berbagai sendi kehidupan sosial di sana, tetapi prinsip hidup ‘Ikhlas’ tetap menjadi hal utama bagi mereka. Meskipun ajaran Islamnya sangat kuat, tetapi para Kyai Kampung ini tidak pernah mengabaikan nilai-nilai tradisi dan kearifan lokal dalam praktek kehidupan sehari-hari.